Multipolar radiofrequency ablation with non‐touch technique for hepatocellular carcinoma ≤ 3 cm: A preliminary report. Issue 3 (4th July 2014) - Wu, Li‐Wei; Chen, Chiung‐Yu; Liu, Chun‐Jen; Chen, Ming‐Yao; Liu, Po‐Chun; Liu, Pan‐Fu; Seror, Olivier; Lee, I‐Lin; Lin, Shi‐Ming
Summary: Background: Conventional monopolar radiofrequency ablation (RFA) bears the risks of incomplete ablation and tumor seeding. This study aimed to evaluate the effectiveness and safety of multipolar RFA with non‐touch technique for hepatocellular carcinoma (HCC) ≤ 3 cm. Methods: Fifteen cirrhotic patients (9 men, 6 women; age 51–83 years, mean 64.4 years, Child‐Pugh score: A = 10 and B = 5) with 17 HCCs of ≤ 3 cm (mean: 26 mm), which were diagnosed based on typical radiologic findings were enrolled. Two or three Celon Prosurge Bipolar electrodes with 3‐cm active tip were deployed with non‐touch technique via percutaneous approach under ultrasound guidance. Results: Complete ablation was achieved in all 17 lesions. This is defined as no enhanced part around the ablated index tumors according to dynamic computed tomography or magnetic resonance imaging at least 1 month after ablation. No local tumor progression was detected at follow‐up (range, 3–21.5 months; mean, 10 months). No track seeding was observed. There was one distant recurrence 15.4 months after ablation. One patient had procedure‐related biliary stricture and died of pneumonia 3.5 months after tumor ablation. Conclusion: Multipolar RFA with non‐touch technique is an effective method to achieve complete tumor ablation and an adequate safety margin. This method has low complication rate and bears minimal risk of tumor seeding.